Population Pharmacokinetics and Pharmacodynamics of Sitafloxacin in Plasma and Alveolar Epithelial Lining Fluid of Critically Ill Thai Patients With Pneumonia - Taniya Paiboonvong; Preecha Montakantikul; Navarat Panjasawatwong; Noppaket Singkham; Baralee Punyawudho (Pharmacology Research & Perspectives)
ABSTRACT Sitafloxacin is one of the oral respiratory quinolones for the treatment of community‐acquired pneumonia. The pharmacokinetic (PK) changes of sitafloxacin in critical illness have been previously reported. However, sitafloxacin exposure and target attainment have never been confirmed in this population. To develop a population pharmacokinetic (PK) model of sitafloxacin, plasma and epithelial lining fluid (ELF) concentrations were obtained after sitafloxacin administration as a 200‐mg single dose under fasting condition in 12 subjects. A population pharmacokinetic analysis was performed using a nonlinear mixed‐effects modeling approach. The probability of target attainment (PTA) and cumulative fraction of response (CFR) against the MIC distribution of S. pneumoniae isolated from Thai patients was estimated by Monte Carlo simulations. The pharmacokinetics of sitafloxacin in plasma was best described by a one‐compartment model linking to the ELF compartment. The partition coefficient which relates drug exposure in ELF to drug exposure in plasma was estimated to be 0.77. Age was a significant covariate that impacted the relative bioavailability. Results from Monte Carlo simulations showed that the maximum approved dose of sitafloxacin 100 mg q 12 h provided > 90% PTA and CFR in both plasma and ELF. The current maximal dosing of sitafloxacin provided adequate exposure in plasma and ELF for the treatment of critically ill Thai patients with pneumonia.